Elevation and Volume Changes in Greenland Ice Sheet From 2010 to 2019 Derived From Altimetry Data - Chen, Guodong; Zhang, Shengjun; Liang, Shenghao; Zhu, Jiaheng (Frontiers in Earth Science, 2021)
Long-term altimetry data is one of the important data sources to analyze the change of global ice reserves. This study focuses on the elevation and volume changes of Greenland Ice Sheet during 2010-2019 derived from altimetry observations. For better results, the methods for determining surface elevation change rates are discussed and specific strategies are designed. A new elevation-difference method is proposed for the slope terrains at the margins of the ice sheet where CryoSat-2 provides interferometric synthetic aperture (SARin) observations is proved to be effective through the validation with Airborne Topographic Mapper (ATM) data. Meanwhile, a Surface-fit method is applied for the flat interior of ice sheet where the low resolution mode (LRM) observations are provided. The results of elevation change rates of Greenland Ice Sheet during 2010 to 2019 are eventually calculated by combining CryoSat-2 and ATM observations. An elevation change rate of -11.83±1.14 cm·a-1 is revealed, corresponding to a volume change rate of -200.22±18.26 km3·a-1. The results are compared with the elevation changes determined by ICESat during 2003 to 2009. Our results show that the overall volume change rate of Greenland Ice Sheet had an approximately 10% slowdown during the past decade and the areas with the most serious ice and snow loss have shifted from the southeast coast to the west margin of the ice sheet.